The Development Of Group Counseling Model Based On Social Cognitive Career Theory To Improve Student's Career Decision Making In The Era Of Society 5.0 - Diana Dewi Wahyuningsih; Mungin Eddy Wibowo; Edy Purwanto; Mulawarman Mulawarman (International Conference on Science, Education, and Technology, 2022)
The era of society 5.0 brought changes to working, this change became a challenge and opportunity for students. Where students are required to be able to keep up with rapid technological advances, this era demans students to be skilled and ability technology and information in various sectors of career and be able to adapt occupation. The ability to make career decisions is an important skill that students must have in the era of society 5.0. Group counseling based on social cognitive career theory can be a model of guidance and counseling services to improve students' career decision-making abilities. This study uses research and development methods involving 484 students, teachers and education practitioners to develop and obtain a hypothetical model. Data collection in this study through interviews, questionnaires and Career Decision Making Self Efficacy Scale. This research produces group counseling model based on social cognitive career theory to improve student career decision making in the society 5.0 era. The process and results of model development are further discussed in this article.